Estudo de parâmetros espectroscópicos de íons de Nd3+ no sistema vítreo SNAB (SiO2 Na2CO3 Al2O3 B2O3) nanoestruturado com nanocristais de CdS - Serqueira, Elias Oliveira (2010)
In this work, experimental evidences have been observed for energy transfer from CdS nanocrystals, synthesized by the fusion method, to Nd3+ ions embedded in vitreous substrates (SNAB: SiO2 Na2O Al2O3 B2O3). These dot samples doped with neodymium have been investigated by combined optical absorption (OA), photoluminescence (PL), and time-resolved photoluminescence (PLRT) techniques. Radiative and non-radiative energy transfers between CdS dot and Nd3+ ion levels, to our knowledge not reported before, can be clearly observed in the PL spectra where the emission band valleys correspond exactly to the energy absorption peaks of the doping ion. The PLRT data reinforce these energy transfer mechanisms in which the increasing overlap between the CdS PL band and the OA to the Nd3+ levels decreases stimulated emissions from the doping ions. The spectroscopic parameter control was observed in Nd3+ ions embedded in a SiO2 Na2O Al2O3 B2O3 glass system. The parameters 2,4,6 Ω and others were determined by the Judd-Ofelt Theory. It was found that these parameters were strongly dependent on Nd3+ concentration, indicating a linking field change. This paper will present and discuss possible mechanisms responsible for changes in the Judd Ofelt parameters. Furthermore, non-radiative energy transfer mechanisms such as energy migration, cross relaxation and losses from networked phonons and OHradicals, will be proposed to explain the observed decrease in 4F3/2 → 4I11/2 transition lifetime of Nd3+. We believe that these results will inspire further investigation of similar systems and allowing possible access devices or applications of lasers.